BENEFITS OF WATCHING MOVIES AND SERIES IN ENGLISH - Kenjaboyeva O`g`iljon To`xtaboy qizi; Ne'matova Madina Baxtiyor qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  This  article  examines  the  educational  and  linguistic  benefits  of watching movies and series in English. It argues that films and TV shows serve as a powerful medium for language acquisition, improving listening, pronunciation, and vocabulary  while  enhancing  cultural  awareness.  By  observing  authentic  speech, learners  develop  natural  fluency  and  grammatical  intuition.  Furthermore,  watching English-language  media  increases  motivation,  promotes  autonomous  learning,  and exposes  learners  to  diverse  accents  and  expressions.  The  article  concludes  that integrating movies and series into language education offers a dynamic, enjoyable, and effective approach to mastering English in the modern world.